Settlement of Default of Muzara’ah Contract of Rice Farmers in Sigama Village, Padang Bolak District, Padang Lawas Utara Regency Dsn-Mui Perspective No. 85/Dsn-Mui/Xii/2012” - Anwar Nuh Siregar; Annisa Sativa (Journal Equity of Law and Governance, 2024)
One of the towns in the Padang Bolak District of the North Padang Lawas Regency, Sigama Village, has extensive agricultural land which is used for rice fields, making farming the main source of income for the local community. But not everyone in the hamlet has agricultural land due to middle to lower class economic factors. Then, the muzara'ah system is one way for people in the area to prioritize mutual cooperation. Muzara'ah is a form of collective agreement between land owners and cultivators for the management of agricultural land, with the parties sharing the results according to their agreement. But the reality in the field is not in accordance with the agreement made between the land owner and the cultivator, where the agreement usually occurs in villages with a profit-sharing system of 70% for the land owner and 30% for the cultivator, with seeds. and fertilizer produced by land owners. In this research, descriptive approach techniques were combined with qualitative methods. Land owners and cultivators are the subjects of this research. Primary and secondary data are used in the data collection process. Meanwhile, secondary data was obtained from previous research, while primary data was obtained through interviews, documentation and observations. Then, the cultivator made a mistake which resulted in the contract being canceled. Then, after long negotiations, none of the parties can reach an agreement, then the dispute is resolved through an institution based on sharia if one party does not reach an agreement. through deliberation.